Geospatial variations and determinants of contraceptive utilization among married reproductive age women in Ethiopia: spatial and multilevel analysis of Ethiopian Demographic and Health Survey, 2019 - Terefe, Bewuketu; Getnet, Mihret; Akalu, Yonas; Belsti, Yitayeh; Diress, Mengistie; Gela, Yibeltal Yismaw; Getahun, Amare Belete; Bitew, Desalegn Anmut; Belay, Daniel Gashaneh (Frontiers in Global Women's Health, 2023)
Abstract Introduction: Contraception is the most effective method of preventing unwanted pregnancies and their disadvantages. It is critical to recognize one's desire to utilize contraceptives before drafting and implementing a good family planning program, especially in developing nations like Ethiopia. Objective: This study aimed to identify the geospatial variations and factors affecting the utilization of contraceptives among married women in Ethiopia Method: This study was based on EDHS. A total of 5,743 married women were included. Because of the hierarchical nature of the DHS data, a multilevel logistic regression model was used. The Bernoulli model was applied by applying Kulldorff methods using the SaTScan software to analyze the purely spatial clusters of contraceptive usage. ArcGIS version 10.3 was used to visualize the distribution of contraceptives. A 95% confidence interval and a p-value of less than 0.05 were used to declare statistical significance. Result: The overall utilization of contraceptives was discovered at 41.25% (39.98, 42.53). Women 25-34 years (AOR=0.80, CI:(0.66,0.96,)) and 35-49 years (AOR=0.50, CI 95%:(0.66,0.96)) times less likely to use contraceptives than 15-24 years old respectively. Having primary (AOR=1.47, CI 95%:(1.25,1.73)), secondary (AOR=1.42, CI 95%:(1.09,1.83)) and higher education level(AOR=1.92, CI 95%:(1.41,2.60)), middle wealth(AOR=1.48, CI 95%:(1.14,1.90)), richer (AOR=1.41, CI 95%:(1.07,1.86)) and richest (AOR=2.17, CI 95%:(1.52,3.11)), having 1-4 ANC follow up have (AOR=1.60, CI 95%:(1.26,2.03)), gave birth at age of 35-44(AOR=0.29, CI 95% (0.22,0.37)), having 3-5 children (AOR=1.26, CI 95%:(1.03,1.52)), being from community of high level women education (AOR=1.61, CI 95% (1.21,2.15)) were associated positively. Participants from Amhara, Oromia, Benishangul and SNNPR regions have revealed (AOR=2.40, CI 95% (1.53,3.77)), (AOR=1.64, CI 95% (1.05,2.56)), (AOR=1.62, CI 95% (1.01,2.62)) and (AOR=2.04, CI 95: (1.31,3.19)), in contrast, Somali and Afar regions have shown (AOR=011, CI 95%:(0.05,0.22)) and (AOR=0.31, CI 95%: (0.18,0.54)) times less likely to use contraceptive services than Tigray Region respectively. Conclusion: The study revealed that contraceptive usage among married women was low, with wide regional variation. Raising awareness among mothers about the importance of antenatal care and assisting mothers who are financially disadvantaged or do not have access to health facilities in providing better family planning services.